A new generation of gas turbine burner systems based on tubular gas combustion technology - Варламов, Геннадий Борисович; Халатов, Артем Артемович; Позняков, П.О.; Юрашев, Д.Н. (Eastern-European Journal of Enterprise Technologies, 2011)
On the basis of theoretical and pilot studies of aerodynamic and thermal processes at the workable assemblies was designed and implemented in the burner systems of GTU combustors a new high-performance and low-emission pipe technology of gaseous fuel combustion.